A Standardised Demon Sequence - Barkowsky, Marie (My University, 2024)
The article discusses a standardised sequence of demons known from multiple incantations and ritual series. While the order of demons included is remarkably stable from attestation to attestation, the number of demons included can vary, leading to some confusion as to how long the standardised sequence was. The article therefore proposes a maximum length of the series and attempts to trace its development from the Old Babylonian period onwards.
PUBLISHED
Keywords: HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of medicine; religion; HUMANITIES and RELIGION::Languages and linguistics::Other languages::Assyriology